Calidad de servicio y la satisfacción del cliente en las compañías de tricimotos del cantón La Maná, provincia de Cotopaxi. Propuesta de un modelo de calidad. - Briones Solís, Mireya Karina (2019)
The general objective of this research was to propose a quality model that would improve the service and raise the level of satisfaction of the customers of the “tricimotos” companies in La Maná. The purpose is to determine the problems in the quality of service provided by the companies of “tricimotos” to their users. According to the existing models, we analyze each of them, in order to know what the advantages and disadvantages are. And so to be able to determine the best model that is adopted to the companies of “tricimotos”; According to the diagnosis, the model of Malcolm Baldrige was proposed to the “tricimotos” companies. Through the research carried out, the detected problems will be reduced through: training, conferences and talks addressed to the members, drivers, administrative personnel; in order to reduce all the anomalies that exist within the organization and thus provide a quality service. Through the field investigation, the deficiencies and difficulties were diagnosed: lack of training, lack of expertise, lack of courtesy, poor service, excess of passengers, speeding among other anomalies; that is why customers are dissatisfied with the service offered by the company. The different trainings addressed to the members and drivers of the “tricimoto” company “19 de Mayo S.A.” in La Maná led to improve the inadequate service they provide.